Sustainable supply chain and performance of firms in the service industry - Tay, Mee Yean (2018)
Malaysia realizes that investing in environmental protection is becoming increasingly important. Businesses can assist in protecting the environment by adopting green business practices or, in other words, by having a sustainable business. The fastchanging world and increasingly unstable working environment mean that building sustainable practices are more important than ever before if organizations are to succeed in the long term. Therefore, the main intention of this study was to investigate the antecedents and consequences of sustainable supply chain management practices in the service industry through the resource-based view (RBV) theory and stakeholder theory. Previous studies only focused on environmental issues, while neglecting the social aspects. Multiple challenges continue to impede the widespread adoption of sustainability across environmental, social, and economic dimensions. Organizations should not underscore how supply chain sustainability translates into measurable business performance. Firms are exposed to the challenges posed by a competitive business environment that is both complex and unpredictable. A lack of knowledge often drives behaviors and practices that produce unsustainable outcomes. The objective of this study was to gauge the antecedents and consequences of sustainable supply chain management (SSCM) practices, which incorporate social, environment and economic aspects, and the moderating effect of knowledge management on firm performance in the Malaysian service industry. Based on 202 usable responses from the service sector, the Statistical Package for the Social Sciences (SPSS) and the partial least squares (PLS) were applied in this study to test the proposed hypotheses. The results showed that service innovation and stakeholder pressure are positively related to SSCM practices. It was found that the social practices of SSCM do not have a significant influence on firm performance. However, the interaction between knowledge management and social practices has a significant influence on firm performance. This study extended the RBV theory by adding service innovation and knowledge management to the context of service firms and enhanced the study of SSCM practices. Besides that, it also extended the stakeholder theory by adding antecedents to assess their influence on SSCM practices. On the practical side, service firms can apply service innovation as a strategy to improve their SSCM practices. Furthermore, service firms should consider having a well-developed knowledge management to strengthen the performance of their firm so as to stay competitive in the future.